Fishes’ composition and captured yield in Sentani Lake Papua - CHAIRULWAN UMAR; SAFRAN MAKMUR (Society for Indonesian Biodiversity, 2006)
Sentani lake is known as lake in Papua where biodiversity of fish is high and captured fisheries activities is dominantly found. The aim of this research was to know the fishes’ composition and captured yield in Sentani lake. This research was done in 2005 by using stratified sampling method which covered 7 (seven) research stations. Data of fishes’ composition and captured yield were obtain from fishers’ captured and from experimental captured. The captured fish and relative abundance are 16 species. Captured yield in period of Mei – December 2005 was fluctuative (130.860 – 182.144 kg). The average was 151.960 kg. Total production a year was around 1.823, 52 ton/year in which fishers’ captured yield was around 4.2 – 5.6 kg/day with the average 4.7 kg/day.© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: fishes’composition, captured yield, Sentani Lake.